2013
DOI: 10.1155/2013/162513
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Properties of Naturally Occurring Polyether Antibiotics

Abstract: Polyether ionophores represent a large group of natural, biologically active substances produced by Streptomyces spp. They are lipid soluble and able to transport metal cations across cell membranes. Several of polyether ionophores are widely used as growth promoters in veterinary. Polyether antibiotics show a broad spectrum of bioactivity ranging from antibacterial, antifungal, antiparasitic, antiviral, and tumour cell cytotoxicity. Recently, it has been shown that some of these compounds are able to selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 115 publications
0
98
0
8
Order By: Relevance
“…The ability of polyether ionophores to control drug-resistant bacteria and parasitic infections is well known, but these compounds also show a broad spectrum of bioactivities, including antifungal, antiviral, antitumor, herbicidal, and anti-inflammatory activities (58,59). In this study, a relatively high number of polyether-producing actinomycetes were isolated, notably the acidophilic streptomycetes (Streptomyces sp.…”
Section: Discussionmentioning
confidence: 97%
“…The ability of polyether ionophores to control drug-resistant bacteria and parasitic infections is well known, but these compounds also show a broad spectrum of bioactivities, including antifungal, antiviral, antitumor, herbicidal, and anti-inflammatory activities (58,59). In this study, a relatively high number of polyether-producing actinomycetes were isolated, notably the acidophilic streptomycetes (Streptomyces sp.…”
Section: Discussionmentioning
confidence: 97%
“…73 Our study began with an exploration to determine a suitable position for the double bond in the R 2 group of the cobalt complex that would avoid undesirable intramolecular Nicholas reactions or elimination reactions. After some experimentation, we found that complex 92 was the most appropriate for carrying out the intermo- Additionally, by using this strategy, we developed a formal synthesis of the enantiomer of the natural product (+)-laurencin (1). 73 This compound is one of the most representative members of the group of lauroxanes, and was first isolated from the extracts of the red algae L. glandulifera by Irie and co-workers in 1965.…”
Section: Scheme 30 Retrosynthetic Analysis Of Cyclic Ethers Based On mentioning
confidence: 99%
“…Zum Vergleich verkapseln elektrogene Ionophore,s ow ie das zyklische Peptid Va linomycin, das Metallion (Kalium im Falle von Va linomycin) als positiv geladenen Komplex und befçrdern das Ion durch die Membran entlang seines Konzentrationsgradienten. Wegen ihrer faszinierenden Eigenschaften [7,8] und potenziellen therapeutischen Anwendungen sind Carboxylpolyether-Ionophore seit vier Jahrzehnten Ziele chemischer Synthesen gewesen, beginnend mit der ersten Totalsynthese von Lasalocid A( 1) von Kishi und Mitarbeitern im Jahr 1978. Außerdem besitzen CPIs auch antibakterielle Aktivität, primärg egen Gram-positive Spezies,u nd zahlreiche Berichte beschreiben ihre Wirkung gegen potenziell medikamentenresistente Bakterienstämme.…”
Section: Introductionunclassified